University science in the US needs a coherent plan - H. Holden Thorp (Science, 2026)
The Trump administration continues to degrade America’s scientific establishment, causing widespread harm to the country’s broader interests and well-being. Last week, the Association of American Universities reported that graduate student enrollment in major research universities, which award half of all doctorate degrees in the United States, is down 15% compared to a year ago. And no wonder, considering the effect of recent immigration policies that deter international students and the financial uncertainties that universities are facing given the unpredictable nature of federal funding. The ability to support new doctoral students depends heavily on research grants, and any responsible administrator would be cautious about making commitments to students they can’t keep. This is discouraging to the scientific community but should be alarming to everyone.